2013
DOI: 10.1007/s13277-013-0710-6
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent chemoradiotherapy with or without adjuvant chemotherapy in intermediate and locoregionally advanced nasopharyngeal carcinoma

Abstract: Concurrent chemoradiotherapy (CCRT) showed a significant improvement in disease control and clinical outcome in patients with intermediate and locoregionally advanced nasopharyngeal carcinoma (NPC) (stage II, III and IVA+B). However, there has been debate about the contribution and application of additional adjuvant chemotherapy (AC) to a CCRT regime. This study aims to evaluate the additional value of AC in the treatment of intermediate and locally advanced NPC with regard to toxicity and clinical outcomes. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Zhang et al . 17 performed a retrospective study to evaluate the value of AC after CCRT for the treatment of NPC. Neither study found a significant benefit in NPC from the addition of AC to CCRT.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al . 17 performed a retrospective study to evaluate the value of AC after CCRT for the treatment of NPC. Neither study found a significant benefit in NPC from the addition of AC to CCRT.…”
Section: Discussionmentioning
confidence: 99%
“…Nasopharyngeal carcinoma (NPC) is a malignant tumor with obvious ethnic aggregation and geographical differences and is one of the most common malignant tumors in southern China and southeast Asia. The incidence of NPC is mainly related to genetic and environmental factors [ 1 , 2 ]. Currently, the 2014 National Comprehensive Cancer Network (NCCN) recommends radiotherapy (RT) alone for early-stage NPC.…”
Section: Introductionmentioning
confidence: 99%
“…The primary treatment for initially untreated nasopharyngeal carcinoma (NPC) is radiotherapy, with or without chemotherapy, and improvements in this approach have led to a continuous increase in survival rate, with a 5-year overall survival (OS) rate from 68.2% to 84.0% for non-metastatic NPC [1,2]. Nevertheless, approximately 8.4-10.9% of NPC patients experience recurrence [3,4].…”
mentioning
confidence: 99%